Learning Difficulties of Slow Learner Students - Sabir, Andi Rifqah; Bahar, Baharullah; Husniati, Andi (Universitas Ahmad Dahlan, 2024)
This study aims to describe learning difficulties in children with special needs of slow learner type, especially in mathematics, through a systematic review of previous research, not based on classroom observations. The type of research used is library research with the Systematic Literature Review method. The data collection technique used is document study, while data analysis is carried out using qualitative content analysis approach. The results of this study reveal that students, including those with special needs of slow learner type, face various difficulties in the learning process at school. This progress is influenced by internal and external factors. Each student faces challenges in understanding concepts, applying principles, and solving verbal problems. This study also shows that students with special needs of slow learner type have difficulty in understanding mathematics lessons, one of which is seen from the level of student intelligence. Further research is needed to identify the factors that cause learning difficulties in students with special needs of slow learner type, so that solutions can be found to overcome obstacles in learning and improve their learning outcomes, especially in mathematics learning.